Sensitivity of bulb tissue section for detection of Fusarium causes Moler disease of shallot. Issue 1 (1st April 2022) - Widono, S; Hadiwiyono; Poromarto, S H; Supyani; Wahyuni, N
Abstract: Moler caused by Fusarium oxysporum f.sp.cepae is a seed-borne disease, so the disease intensity in the field is depend on the amount of initial inoculum in the infected bulbs as seeds. Therefore, the detection of seed-borne pathogens is important to determine the potential of their transmission. The aim of this research was to evaluate the sensitivity of the bulb tissue of shallot based on the pathogen Infection Index by incubation method on agar media to detect the presence of F. oxysporum f.sp. cepae. The experiment was conducted using a completely randomized design with five replications and three varieties of shallots (Thailand, Bima, and Bauji). Each treatment unit was placed in a Petri's dish with a diameter of 20 cm, containing 40 mL PDA on which 16 pieces of the tip, middle, and base of the bulb tissues were placed, which were incubated for 7 days. Pathogen Infection Index is a parameter that was observed macroscopically and microscopically. The results showed that the base of the bulbs tissue section of the three varieties tested showed higher sensitivity than the other part to detect the presence of F. oxysporum f.sp. cepae in shallot. It indicates that the basal bulb is the major infection side of the pathogen.